Judicial politics and urban revolt in seventeenth-century France : the Parlement of Aix, 1629-1659 - Kettering, Sharon, 1942- (Princeton legacy library., 1978)
Most historical scholarship concerned with the Fronde has investigated the Parlement of Paris. By focusing on the different experience of high court judges in Aix-en-Provence, Sharon Kettering illuminates the causes of resistance to royal authority and offers a new understanding of the role of provincial officials in seventeenth-century revolts. The author shows that political tensions and alignments within the court and provincial capital were as important in causing the revolts at Aix as the judges' relationship with the crown. Describing the liaisons and personalities that gave impetus t.